Psychoanalytic study on the main character in Nizami Ganjavi’s Layla Majnun And William Shakespeare’s Romeo Juliet: A Comparative Literature - Albab, Mohammmad Ulul (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Comparative literature is a branch of literary science that examines literature in various forms, functions, and meanings. This article tries to review from the aspect of Literary Psychology of two literature being compared, the novel